2019
DOI: 10.3390/ijerph16234665
|View full text |Cite
|
Sign up to set email alerts
|

Enrichments of Cadmium and Arsenic and Their Effects on the Karst Forest Area

Abstract: An understanding of the enrichment mechanisms of cadmium (Cd) and arsenic (As) in the process of rock weathering and soil formation is essential to develop agriculture according to local conditions. However, the enrichments of soil Cd and As under natural background conditions in karst areas are still uncertain. The enrichment factor, geo-accumulation index, redundancy analysis, and other methods were used to analyze the enrichment degree and the influencing factors of Cd and As on 5 rock–soil profiles and 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 36 publications
(35 reference statements)
2
2
0
Order By: Relevance
“…The high values in Damietta and Kafr Saad regions may be attributed to the high rates of phosphorus fertilization application and irrigation with sewage effluent or mixed water. These findings are agreed with several research work 48,49 and they reported that sewage sludge, soil organic matter and phosphorus fertilizers are important factors that influenced the enrichments of Cd in the topsoil. Frequency distribution of total Cd in the studied soils shows that 26% of the studied soils contained values of total Cd less than 500µg kg -1 (Figure 5).…”
Section: Soil Total CD Contentsupporting
confidence: 93%
See 1 more Smart Citation
“…The high values in Damietta and Kafr Saad regions may be attributed to the high rates of phosphorus fertilization application and irrigation with sewage effluent or mixed water. These findings are agreed with several research work 48,49 and they reported that sewage sludge, soil organic matter and phosphorus fertilizers are important factors that influenced the enrichments of Cd in the topsoil. Frequency distribution of total Cd in the studied soils shows that 26% of the studied soils contained values of total Cd less than 500µg kg -1 (Figure 5).…”
Section: Soil Total CD Contentsupporting
confidence: 93%
“…Under such conditions the solubility of Cd in the surface soil layers and its downward movement to the soil subsurface layers increases. This agree with Wang et al 48 which reported that soil organic matter important is factors that influenced the enrichments of Cd in the soil.…”
Section: Soil Dtpa Extractable CDsupporting
confidence: 92%
“…A study on the remote Northern Sakhalin region of Russia found arsenic concentrations built up to 9.2 mg/kg in the surface organic horizons of peats and podzols of forest settings, with an average of 2.8 mg/kg . Wang et al found high concentrations of arsenic in the humic horizon of a forest soil in southeast China of 27 mg/kg. They concluded that this enrichment originated from a limestone bedrock concentration of 8.6 mg/kg, stating that internal biogeochemical cycling was responsible, i.e., plant assimilation and bioconcentration of soil arsenic, without providing evidence.…”
Section: Sources and Trends In Atmospheric Arsenic And Subsequent Dep...mentioning
confidence: 99%
“…Additionally, while planned logging (e.g., transforming natural forests into oil palm forests or timber forests) may stop significant net forest loss, it diminishes the forest's ecological value and degrades many of its ecosystem services [17][18][19][20]. Among regions with extensive and highly developed heavy industries and mining activities, environmental pollution (e.g., soil and water pollution) can lead to significant permanent forest loss [21,22]. For many developing countries, urban construction is the main cause of forest loss.…”
Section: Introductionmentioning
confidence: 99%